Monuments of everyday life. Interplays of city, infrastructure and architecture in São Paulo. - Hartmann, Sarah (Jovis, 2019)
Monumente üben seit jeher eine besondere Faszination aus, sie speichern Erinnerungen, dienen als Aufenthaltsorte und markieren Orientierungspunkte in der Stadt. Doch welche gesellschaftlichen und kulturellen Werte manifestieren sich heute in Monumenten, besonders in explosiv gewachsenen urbanen Kontexten? Wie können Architekten und Stadtplaner diese wichtige Entwurfsaufgabe zeitgemäß denken? "Monuments of Everyday Life" ist eine Neuinterpretation des Konzepts "Monument": Ausgehend von vier vielschichtigen Orten in der Megacity São Paulo analysiert die Autorin räumliche Muster und zeigt auf, wie Monumente auch heute kollektive Bezugspunkte der Stadtgesellschaft sein können - und lebendige Alternativen zu Orten der Instabilität, Kommerzialisierung und Homogenisierung. Das Buch zieht nicht nur Rückschlüsse aus der Vergangenheit, sondern befasst sich darüber hinaus eindrucksvoll mit den Potenzialen und zukünftigen Fragen städtischer Räume.

Monuments have fascinated human beings and enriched cities throughout different periods and in various forms as repositories of history and memories, as places to spend time, as meeting points, and as points of orientation. However, as a major component of the discipline of architecture and urban design, the term "monument," along with ist relationship to the city, is in crisis. This book explores a rediscovery of the concept of monuments as essential and creative parts of cities. The ideas in "Monuments of Everyday Life" are outlined by the rereading of four powerful, multifaceted urban locations in São Paulo. It reveals the specific spatial patterns around monuments, which are understood as alternatives to places of instability and the commercialisation and homogenisation of urban space. It discusses the relevance of monuments as reference points for collective life and material representatives of collective values. Monuments of Everyday Life draws conclusions from the past but more than that, it addresses relevant questions and possibilities concerning urban futures.
Keywords: Stadtsoziologie; Stadtstruktur; Großstadt; Stadtraum; Öffentlicher Raum; Aufenthaltsqualität; Stadtbewohner; Stadtgesellschaft; Urbanität; Raumnutzung; Raumaneignung; Architektur